Global disease burden and trends of leukemia attributable to occupational risk from 1990 to 2019: An observational trend study - Shi, Yuanfei; Chen, Can; Huang, Yamei; Xu, Yi; Xu, Dandan; Shen, Huafei; Ye, Xiujin; Jin, Jie; Tong, Hongyan; Yu, Yue; Tang, Xinyi; Li, Azhong; et al. (Frontiers in Public Health, 2022)
Background: Leukemia caused by occupational risk is a problem that needs more attention and remains to be solved urgently, especially for acute lymphoid leukemia (ALL), acute myeloid leukemia (AML), and chronic lymphoid leukemia (CLL). However, there is a paucity of literature on this issue. We aimed to assess the global burden and trends of leukemia attributable to occupational risk from 1990 to 2019. Methods: This observational trend study was based on the Global Burden of Disease (GBD) 2019 database, the global deaths and disability-adjusted life years (DALYs), which were calculated to quantify the changing trend of leukemia attributable to occupational risk were analyzed by age, year, geographical location and socio-demographic index (SDI) and calculated the corresponding estimated annual percentage change (EAPC) values. Results: Global age-standardized DALYs and death rates of leukemia attributable to occupational risk presented significantly decline trends with EAPC (-0.38% [95% CI: -0.58% - -0.18%] for DALYs and -0.30% [95% CI: -0.45% - -0.146%] for death). However, it was significantly increased in people≥70 years old (0.79% [95% CI:0.69% - 0.88%] for DALYs and 0.74% [0.64% - 0.84%] for death). At the same time, the age-standardized DALYs and death rates of ALL, AML and CLL were presented a significantly increase trends with EAPCs (0.78% [95% CI:0.65% - 0.91%], 0.87% [95% CI:0.81% - 0.93%], and 0.66% [95% CI:0.51% - 0.81%] for DALYs, respectively and 0.75% [95% CI:0.68% - 0.82%], 0.96% [95% CI:0.91% - 1.01%], and 0.55% [95% CI:0.43% - 0.68%] for death, respectively. The ALL, AML, CLL were shown an upward trend and in all age groups. Conclusion: We observed a substantial reduction in leukemia due to occupational risks between 1990 and 2019. However, the people≥70 years old and ALL, AML and CLL of all ages had a significantly increased trend. Thus, there remains an urgent need to accelerate efforts to reduce leukemia attributable to occupational risk-related death burden in this population and specific causes.